Effects of strength, speed and non-specific resistance training on athletic performance and FVP profile characteristics of youth professional soccer players - Ribic, A.; Pleša, J.; Ujakovic, F.; Kozinc, Ž. (International Journal of Strength and Conditioning, 2025)
This study explored the effects of strength-focused, speed-focused, and non-specific resistance training on the athletic performance and sprint biomechanics through force-velocity-power (FVP) profile in youth professional soccer players (age: 17.6 ± 0.9 years). In a 6-week randomized-controlled trial, 24 male participants were assigned to strength, speed, or control groups (n = 8 each). We assessed sprint performance, including sprint split times and the sprint FVP profile. Post-training, all groups showed significant enhancements in sprint times (p = 0.000-0.004, n² = 0.32-0.75) and FVP profile variables (p = 0.000-0.049; n² = 0.17-0.73). The strength group exhibited notable improvements in the maximal ratio of horizontal-to-resultant force (p = 0.026, d = 0.78) and maximal power (Phmax) (p = 0.013, d = 0.89) compared to controls. However, maximum velocity and maximum velocity at the end of acceleration phase did not significantly change in any group. These findings demonstrate that both strength and speed training significantly enhance force production capabilities in youth soccer players, influencing key FVP profile characteristics, without substantially affecting maximum velocity.